Pengaruh Citra, Kepercayaan Anggota, dan Kualitas Pelayanan Terhadap Partisipasi Anggota KPRI Megar - Ni'mah, Naelatun; Rusdarti, Rusdarti (Business and Accounting Education Journal, 2021)
KPRI Megar is a civil servant cooperative consisting of elementary school teachers throughout Rembang District, Purbalingga Regency. This study aims to analyze: (1) the influence of the image on member participation, (2) the influence of member trust on member participation, (3) the influence of service quality on member participation, (4) the influence of image, member trust, service quality together same for member participation. The population of this research is 217 cooperative members. The number of samples from this research is 98 members with simple random sampling technique. This study uses a quantitative approach with a method of collecting data in the form of a questionnaire. The data analysis method used is descriptive percentage statistics and multiple regression. The results showed that simultaneous image, member trust, and service quality had an effect on member participation by 81.7% and the remaining 18.3% was influenced by other factors not examined in this study. Partially the image has an effect of 20.52%, member trust has an effect of 18.06%, and service quality has an effect of 29.59% on the participation of members of KPRI Megar. Suggestions that can be given to cooperatives are expected to improve the quality of services for their members, image and trust in developing cooperatives.